Hubble Space Telescope [O iii] emission-line kinematics in two nearby QSO2s: a case for X-ray feedback. Issue 2 (28th May 2021) - Trindade Falcão, Anna; Kraemer, S B; Fischer, T C; Crenshaw, D M; Revalski, M; Schmitt, H R; Maksym, W P; Vestergaard, M; Elvis, M; Gaskell, C M; Hamann, F; Ho, L C; et al.
ABSTRACT: We present a dynamical study of the narrow-line regions in two nearby type 2 quasars (QSO2s). We construct dynamical models based on detailed photoionization models of the emission-line gas, including the effects of internal dust, to apply to observations of large-scale outflows from these active galactic nuclei (AGNs). We use Mrk 477 and Mrk 34 in order to test our models against recent Hubble Space Telescope ( HST ) Space Telescope Imaging Spectrograph (STIS) observations of [O iii ] emission-line kinematics, since these AGNs possess more energetic outflows than found in Seyfert galaxies. We find that the outflows within 500 pc are consistent with radiative acceleration of dusty gas, however the outflows in Mrk 34 are significantly more extended and may not be directly accelerated by radiation. We characterize the properties of X-ray winds found from the expansion of [O iii ]-emitting gas close to the black hole. We show that such winds possess the kinetic energy density to disturb [O iii ] gas at ∼1.8 kpc, and have sufficient energy to entrain the [O iii ] clouds at ∼1.2 kpc. Assuming that the X-ray wind possesses the same radial mass distribution as the [O iii ] gas, we find that the peak kinetic luminosity for this wind is 2 per cent of Mrk 34's bolometric luminosity, which is in the 0.5–5 per cent range required by some models for efficient feedback. Our work shows that, although the kinetic luminosity as measured from [O iii ]-emitting gas is frequently low, X-ray winds may provide more than one order of magnitude higher kinetic power.